Fostering Entrepreneurial Learning through Authentic Assessment in a Self-Directed Learning Environment: A Systematic Literature Review - Kamanga, Effiness Harawa; Kruger, Danel NA (International Journal of Learning, Teaching and Educational Research, 2025)
Entrepreneurial learning fosters value creation beyond traditional business-orientated aims but remains underdeveloped in South African schools. With rising youth unemployment and dropout rates, there is a need for alternative strategies to equip learners for success in business and life. Self-directed learning promotes autonomy and the skill sets required for entrepreneurial learning, while authentic assessment connects learning to the needs of the community and workplace. However, there is scant research that explores the way the practice of authentic assessment in self-directed learning environments can support entrepreneurial learning. This systematic literature review explores how entrepreneurial learning can be fostered through authentic assessment in self-directed learning environments in South African secondary schools. Inclusion criteria were used to select existing literature on authentic assessment, self-directed learning and entrepreneurial learning and examine it to map out key processes for implementing authentic assessment in self-directed learning environments that teachers can use as a guide to foster entrepreneurial learning. After completing the literature search and screening process, 23 studies were analysed using a thematic synthesis approach. The findings identified key design principles that provide a conceptual basis for integrating authentic assessment practices into self-directed learning to foster entrepreneurial learning that is applicable across various secondary school subject areas. https://doi.org/10.26803/ijlter.24.10.12